U-NUMBERS IN FIELDS OF FORMAL POWER SERIES OVER FINITE FIELDS. Issue 2 (29th April 2020) - KEKEÇ, GÜLCAN
Abstract : In the field K of formal power series over a finite field K, we consider some lacunary power series with algebraic coefficients in a finite extension of K(x) . We show that the values of these series at nonzero algebraic arguments in K are U -numbers.